Evaluation of a micro ionization chamber for dosimetric measurements in image-guided preclinical irradiation platforms. (10th December 2021) - Silvestre Patallo, Ileana; Carter, Rebecca; Maughan, David; Nisbet, Andrew; Schettino, Giuseppe; Subiel, Anna
Abstract: Image-guided small animal irradiation platforms deliver small radiation fields in the medium energy x-ray range. Commissioning of such platforms, followed by dosimetric verification of treatment planning, are mostly performed with radiochromic film. There is a need for independent measurement methods, traceable to primary standards, with the added advantage of immediacy in obtaining results. This investigation characterizes a small volume ionization chamber in medium energy x-rays for reference dosimetry in preclinical irradiation research platforms. The detector was exposed to a set of reference x-ray beams (0.5–4 mm Cu HVL). Leakage, reproducibility, linearity, response to detector's orientation, dose rate, and energy dependence were determined for a 3D PinPoint ionization chamber (PTW 31022). Polarity and ion recombination were also studied. Absorbed doses at 2 cm depth were compared, derived either by applying the experimentally determined cross-calibration coefficient at a typical small animal radiation platform 'user's' quality (0.84 mm Cu HVL) or by interpolation from air kerma calibration coefficients in a set of reference beam qualities. In the range of reference x-ray beams, correction for ion recombination was less than 0.1%. The largest polarity correction was 1.4% (for 4 mm Cu HVL). Calibration and correction factors were experimentally determined. Measurements of absorbed dose with the PTW 31022, in conditions different from reference were successfully compared to measurements with a secondary standard ionization chamber. The implementation of an End-to-End test for delivery of image-targeted small field plans resulted in differences smaller than 3% between measured and treatment planning calculated doses. The investigation of the properties and response of a PTW 31022 small volume ionization chamber in medium energy x-rays and small fields can contribute to improve measurement uncertainties evaluation for reference and relative dosimetry of small fields delivered by preclinical irradiators while maintaining the traceability chain to primary standards.